Mammalian Diversity and Matses Ethnomammalogy in Amazonian Peru. Part 1: Primates - Farid Pazhoohi (Ethnobiology Letters, 2011)
Review of Mammalian Diversity and Matses Ethnomammalogy in Amazonian Peru. Part 1: Primates. Robert S. Voss and David W. Fleck. 2011. Bulletin of the American Museum of Natural History, Number 351. Pp.81, 3 figures, 25 tables. Free at AMNH Digital Library ISSN 0003‐0090.